THE SOUNDS OF AFRICAN-AMERICAN IN MAYA ANGELOU’S POEMS: ALONE, STILL I RISE, CAGED BIRD AND EQUALITY - PALUPI, NGESTI RETNO (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: The Sounds of African-American, Genetic Structuralism, MayaAngelouThe differences among human brings the issue about race which the concept about race emerges racism. One big issue about race is AfricanAmericans were got the racial discrimination and they became the minority in the United States. The writer wants to examine the sounds of minority which reflect in Maya Angelou’s poems. The writer chose Maya Angelou’s poem since she is the most influence African-American woman through her works, especially in poetry. The problem to be solved in this study is: how does Maya Angelou reflect the sounds of African-American that she writes on her poems; Alone, Still I Rise, Caged Bird, and Equality?The writer applies Goldmann’s theory which is genetic structuralism in analyzing the intrinsic and extrinsic element of Maya Angelou’s poems. From Goldmann’s theory it is clearly mentioned that literary work could not be separated from the intrinsic and extrinsic element because the historical background of the author as the member of social group always give influenced to the work.The result of this research is found that there are three sounds of AfricanAmericanthat reflect in Maya Angelou’s poems: First, the sound of freedom that represent in Caged Bird, second, the sound of equality that represent in Equality, and third, the sound of racism that represent in Alone and Still I Rise.In the future, if there is a researcher who would like to analyze the same object, it is suggested to use post-colonial theory. By using post-colonial theory, it will help to reveal the effect of racial discrimination that happen toward African American life and their society.